Indicators of Social Sustainability in The Airport Terminal Infrastructure - Umi Fadhilah Dhuha; Mohammad Arif Rohman (Universitas Batanghari Jambi, 2026)
Infrastructure development, including airport terminals, is increasing in Indonesia. This development is carried out to support the needs of the Indonesian people and facilitate connectivity between regions. The application of sustainable development principles in the construction sector has become an urgent need, along with the increasing awareness of the long-term impact of public infrastructure on society. Social sustainability is crucial to consider in construction, especially airport terminal infrastructure, because public infrastructure directly interacts with the needs and satisfaction of the community as end users. This study was conducted to identify and define social sustainability criteria applied to airport terminal infrastructure. This study uses primary data obtained from a questionnaire survey containing social sustainability criteria for airport terminal infrastructure. This study focuses on the operational and maintenance phase of the construction project. Data were collected by distributing questionnaires to airport operators, construction service providers, and international airport users. The method used in this study began with variable synthesis, a preliminary survey, a pilot test, and continued with the main survey. These variables were analyzed using mean and standard deviation tests. This research identified 21 relevant indicators to measure the social sustainability of airport terminal buildings. The most important social sustainability indicator is the indicator that the airport terminal provides a sense of security for users against threats and dangers. Further research can be conducted by developing a framework for assessing the social sustainability aspects of airport terminals.